Meta-Analysis of Determinants of the Incidence of Polycystic Ovarian Syndrome (PCOS) in Indonesia - Nira Khayati; Cusmarih Cusmarih (Global Health Science Group, 2023)
In 2013 the infertility rate in Indonesia has increased to 15-25% of all married couples or 4 to 6 million couples require infertility treatment to get offspring. Infertility in women is generally caused by ovulation disorders, one of the causes of ovulation disorders is Polycystic Ovary Syndrome (PCOS). PCOS is caused by various factors or determinants. The purpose of this study was to analyze the influence of determinants of obesity, stress and employment status factors on the incidence of PCOS in women in Indonesia. This study was conducted with systematic review and meta-analysis. Research data is searched from: PubMed and google scholar. By using the search keywords